Superiority of zinc complex of acetylsalicylic acid to acetylsalicylic acid in preventing postischemic myocardial dysfunction: $hSevil Korkmaz, Ayhan Atmanli, Shiliang Li, Tamás Radovits, Peter Hegedűs, Enikő Barnucz, Kristóf Hirschberg, Sivakkanan Loganathan, Yutaka Yoshikawa, Hiroyuki Yasui, Matthias Karck and Gábor Szabó - Korkmaz-İçöz, Sevil; Atmanli, Ayhan; Li, Shiliang; Radovits, Tamás; Hegedűs, Péter; Barnucz, Enikő; Hirschberg, Kristóf; Loganathan, Sivakkanan; Yoshikawa, Yutaka; Yasui, Hiroyuki; Karck, Matthias; Szabó, Gábor (Experimental biology and medicine, 2015)
The pathophysiology of ischemic myocardial injury involves cellular events, reactive oxygen species, and an inflammatory reaction cascade. The zinc complex of acetylsalicylic acid (Zn(ASA)2) has been found to possess higher anti-inflammatory and lower ulcerogenic activities than acetylsalicylic acid (ASA). Herein, we studied the effects of both ASA and Zn(ASA)2 against acute myocardial ischemia.
Gesehen am 21.07.2020